ALCOHOL SENSING ALERT WITH ENGINE LOCKING SYSTEM - Krishnan, Aparna; B, Dhanya T; Anoob, Umaiba; R, Deepa V; MG, Gireeshan (International Journal of Psychosocial Rehabilitation, 2020)
Driving under the influence of alcohol has affected and killed countless of people’s lives. If you drink and drive, not only do you possibly put yourself at risk, but your passengers, and other pedestrians, who were on road every thirty minutes and someone’s life is cut short and families are devastated…So here we implemented a prototype version Alcohol detection system in order to control drunk and driving as much as we can.This alcohol detection system works on a simple principle, if a driver has been drinking, the alcohol is in the driver’s breath and if it crosses a set threshold, an alert will come and the vehicle engine speed reduces gradually and stop immediately. In between the stopping time and alert ringing time, it is safe to steer off the vehicle aside. This project is designed for the safety of the people seating inside/outside the vehicle.